STASIUN PENGISIAN MOBIL LISTRIK BERBASIS PANEL SURYA - Panji Waskita; Dinda Amalia Azahra; I Made A Setiawan; Surojo Surojo (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
This study designs an electric car battery charging system using solar panels and calculates the cost or tariff charged from the charging. The method used in making this research is data collection, testing and data analysis. Solar panels as a source of supply absorb sunlight and convert it into electrical energy. Then the buck-boost converter regulates the voltage that will enter the battery to match the required charging voltage. The test was carried out using a 12 Volt 7 Ah battery, so the required voltage was at least 13 Volts to be able to carry out the charging process. The length of charging time depends on the current generated, the greater the current flowing, the faster the charging process will be. The current sensor and voltage sensor INA219 are used to read the current and voltage that enter during the battery charging process and are controlled by Arduino Mega 2560. When the battery is full the current will be cut off automatically using a relay. This tool is also equipped with inputs in the form of start, stop and reset buttons so that the charging process can be more efficient. The calculation of the cost or tariff for charging an electric car follows the regulation of the Minister of Energy and Mineral Resources (ESDM), which is Rp. 1,650 per kWh. The cost calculation in the electric car charging process is displayed on the display using an 20x4 LCD.